O-B03 Bariatric Surgery in Patients Awaiting a Kidney Transplant - Systematic Review and Personal Experience from a High Volume Bariatric Centre. (16th December 2021) - Hamaoui, Karim; Russell, Neil; Al-Rashedy, Mohammed; Al-Taan, Omer
Abstract: Background: Morbid obesity in end stage renal disease (ESRD) is a barrier to kidney transplantation due to potential suboptimal post-transplant outcomes. Bariatric surgery is the most effective treatment for morbid obesity and has been shown to improve transplant eligibility through weight loss. There is no national UK guidance with regards to the role of bariatric surgery in patients requiring a kidney transplant. We present a decade of experience from a large NHS tertiary referral bariatric centre of performing bariatric surgery for weight loss in a cohort of high BMI ESRD patients. Methods: A retrospective review was conducted of all patients undergoing bariatric surgery between 2007-2017. All patients with chronic kidney disease (CKD) at the time of bariatric surgery were identified. Patient records for those with CKD stage 4 and Stage 5 (or ESRD) were reviewed and data extracted for analysis. A systematic review was also conducted of reported experiences of bariatric surgery in CKD patients as a bridge to kidney transplantation. Results: Of 3119 patients operated on in the identified period 22 were identified as having CKD at the time of surgery. Sleeve gastrectomy was the most commonly performed procedure. There was no recorded post-operative complications or 30-day mortalities. Median LOS was 4 days (range:2-6), pre-operative BMI 45 (Range:37-69), 12m post-op excess weight loss 17.3±14.4%, final EWL 22.3±14.8% at 32 months follow-up (Range: 6-52). 57% were subsequently transplant wait listed, 28% proceeded to transplantation 18.5months after listing (Range:7-30months). Systematic review of 15 studies suggests bariatric surgery in these patients is safe and facilitates 1/4 of patients being listed and transplanted. Conclusions: Experience from a large UK NHS bariatric centre shows weight-loss surgery in high BMI patients with CKD4/5 is safe, with minimal peri-operative morbidity and mortality. 1 in 2 patients proceeded to being listed for transplantation, and 1 in 3 progressed to transplantation. We should consider formalising the role of bariatric surgery in the pre-listing workup of high BMI ESRD patients in the UK to give all patients equal chances for transplantation.